Iron-based micro-electrolysis filler as well as preparation method and application thereof

By using polyester raw materials in iron-carbon microelectrolytic fillers to prepare porous ceramic particles and load nano-ferrous, and then coated with conductive polymer protective coating, the problem of rusted plate bonding of fillers is solved, and the conductivity and wastewater treatment effect are improved.

CN119898861AActive Publication Date: 2025-04-29XIAN EUREKA ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510313420.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2025-03-17
Publication Date
2025-04-29
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

Iron-carbon microelectrolytic fillers are prone to rust and bonding during operation, reducing the effect of sewage treatment, and limiting the promotion and application of microelectrolytic technology.

Method used

Polyester raw materials are prepared by transesterification method, and porous ceramates are formed by water-cooled pore formation, and loaded nanoferric is deposited through atomic layer. Finally, the surface of which is sprayed with silica-modified polyaniline conductive polymer solution to form a conductive polymer coating to protect the iron element.

Benefits of technology

The problem of rusting and tangled plates caused by the direct contact between iron-based microelectrolytic filler iron materials and wastewater is solved, and the conductivity of the filler and the wastewater treatment effect is improved, and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005315232670000111
    Figure BDA0005315232670000111
  • Figure BDA0005315232670000112
    Figure BDA0005315232670000112
  • Figure BDA0005315232670000121
    Figure BDA0005315232670000121
Patent Text Reader

Abstract

The invention relates to the field of water treatment materials, and particularly discloses an iron-based micro-electrolysis filler and a preparation method and application thereof.The preparation method comprises the following steps that aromatic diacid and aliphatic diol serve as raw materials, and a polyester raw material is prepared through a transesterification method; the preparation method comprises the following steps: heating and melting a polyester raw material under the protection of nitrogen, quickly cooling with water, cutting to obtain spherical ceramsite, and drying to obtain porous ceramsite; preparing modified ceramsite loaded with nano-iron: carrying out atomic layer deposition treatment to enable the nano-iron to be evaporated, deposited and loaded on the porous ceramsite, so as to prepare the modified ceramsite; preparing the iron-based micro-electrolysis filler: spraying a silicon dioxide modified polyaniline solution on the modified ceramsite, and curing to obtain the iron-based micro-electrolysis filler; the invention further discloses the iron-based micro-electrolysis filler prepared through the preparation method and application of the iron-based micro-electrolysis filler in water treatment, the problem that the sewage treatment effect is reduced due to the fact that an existing iron-carbon micro-electrolysis filler is prone to rusting and hardening in the operation process is solved, and the wastewater treatment effect of micro-electrolysis is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of water treatment technology, and more specifically, to an iron-based micro-electrolysis filler and a preparation method and application thereof. Background Art

[0002] With the rapid development of industry, various industrial wastewater treatment issues have become increasingly prominent. In the field of wastewater treatment, my country's water treatment technology is mainly based on biological methods, but toxic and difficult-to-degrade organic matter in industrial wastewater is often difficult to treat by biological methods to meet discharge standards. Even if chemical oxidation is used, it is difficult to completely degrade some large molecular organic matter into inorganic matter.

[0003] At present, micro-electrolysis technology is based on the synergistic treatment effect of redox reaction, which realizes the chain breaking of macromolecular organic matter in wastewater and the reduction of oxidized substances, so as to degrade or remove organic pollutants in wastewater and improve the biodegradability coefficient of wastewater to achieve the purpose of pre-treating wastewater. Because of its simple process and convenient operation, it is a wastewater treatment technology that has been widely studied and applied. At present, the more mature chemical reduction process studied at home and abroad is the iron-carbon micro-electrolysis method, whose mechanism mainly includes the electrochemical catalysis of the cathode, direct reduction of iron, reduction of new ecological H, polymerization precipitation of hydroxy-iron complexes, etc. Engineering applications have shown that this method has a good effect on the removal of difficult-to-degrade organic pollutants in industrial wastewaters such as dye wastewater, printing and dyeing wastewater, papermaking wastewater, and chemical wastewater.

[0004] However, with the development of iron-carbon micro-electrolysis technology, its defects in wastewater treatment engineering applications have gradually become apparent. At present, iron-carbon micro-electrolysis fillers are mainly composed of iron powder and carbon powder in a specific ratio, and are combined with auxiliary raw materials such as porogens, adhesives and catalysts. After the iron-carbon micro-electrolysis fillers are operated in wastewater projects for a period of time, the iron materials in direct contact are prone to rust and hardening during use, reducing the sewage treatment effect and restricting the promotion and application of micro-electrolysis technology. Summary of the invention

[0005] In order to solve the problem that the current iron-carbon micro-electrolysis filler is prone to rust and compaction during operation, which reduces the sewage treatment effect and improves the treatment effect of micro-electrolysis on wastewater, the present application provides an iron-based micro-electrolysis filler and its preparation method and application.

[0006] In a first aspect, the present application provides a method for preparing an iron-based micro-electrolytic filler, using the following technical solution: A method for preparing an iron-based micro-electrolysis filler comprises the following steps: S1. Preparation of polyester raw materials: using aromatic diacids and aliphatic diols as raw materials, preparing polyester raw materials by ester exchange method; S2, preparing porous ceramsite: heating and melting the polyester raw material to 200-240°C under nitrogen protection, and then rapidly cooling it in water at 0-5°C, cutting it into spherical ceramsite after solidification by water cooling, and drying it to obtain porous ceramsite; S3, preparing modified ceramsite loaded with nano-iron: using atomic layer deposition to allow nano-iron to evaporate and deposit on porous ceramsite to obtain modified ceramsite; S4, preparing iron-based micro-electrolytic filler: spraying the silicon dioxide-modified polyaniline solution on the modified ceramsite prepared in step S3, and curing the solution to obtain the iron-based micro-electrolytic filler.

[0007] By adopting the above technical scheme, the present application uses polyester raw materials as a basis, undergoes water-cooling pore-inducing treatment, and produces a large number of tiny cracks and pores inside the polyester raw materials through rapid high and low temperature conversion to obtain porous ceramsite, and controls the water cooling temperature to control the water cooling rate, thereby obtaining porous ceramsite with a better pore structure; and then uses atomic layer deposition to load nano-iron on the surface of the porous ceramsite; Finally, a silica-modified polyaniline conductive polymer solution is sprayed on its surface to form a conductive polymer coating. The coating of the conductive polymer coating also solves the problem of direct contact between the iron material of the iron-based micro-electrolytic filler and the wastewater, thereby causing rust and plate formation. At the same time, the coating is a conductive polymer and will not affect the micro-electrolysis effect of the iron-based micro-electrolytic filler. In addition, the use of silica-modified polyaniline solution for coating also improves the conductivity of the iron-based micro-electrolytic filler, better transmits current, thereby accelerating the electrolysis reaction, and having a better treatment effect on wastewater.

[0008] In summary, the iron-based micro-electrolysis filler provided in the present application realizes a change in the current form of adding iron elements to the anode. The iron-based micro-electrolysis filler in the present application uses a porous structure formed by polyester as a carrier to realize the loading of nano-iron, and then realizes the protection of the iron element through a conductive polymer protective coating, thereby solving the problem that the treatment effect is reduced due to the viscosity surrounding it when it is in direct contact with water. The silica in the conductive polymer protective coating serves as a dispersant, and polyaniline serves as a continuous conductive phase, which improves the conductivity through its electron transfer channel function. The pore structure and hydrophilicity of the silica in the protective coating make it water permeable and can form a micro-electrolysis effect with a carbon source, while blocking impurities such as clay, thereby solving the current problem that the treatment effect is reduced due to the direct contact of the iron element with water.

[0009] Optionally, in step S1, the aromatic diacid is a mixture of terephthalic acid and isophthalic acid, and the added mass ratio of terephthalic acid to isophthalic acid is 60:(30-50); The aliphatic diol is a mixture of 1,4-butanediol and 1,6-hexanediol, and the added mass ratio of 1,4-butanediol to 1,6-hexanediol is 55:(40-50); The added mass ratio of the aromatic diacid to the aliphatic diol is 1:(1-1.2).

[0010] By adopting the above technical scheme, the addition of isophthalic acid in the aromatic diacid improves the toughness and flexibility of the polyester raw material molecules, which is beneficial to the occurrence of microcracks in the subsequent processing of the polyester raw material, while the addition of 1,4-butanediol and 1,6-hexanediol increases the flexibility of the polyester main chain. The molecular weight of the polyester finally obtained is greater than 35,000, the molecular weight distribution index is 1.8-2.2, the melt index is 220-240℃, it has high thermoplasticity, and the crystallinity is less than 30%. After subsequent water-cooling pore-inducing treatment, the pore distribution of the porous ceramsite is better, and the loading amount and loading uniformity of nano-iron are better. Finally, the iron-based micro-electrolysis filler is more effective in removing organic matter from wastewater.

[0011] Optionally, in step S1, the specific operation of transesterification is: The raw materials are heated to melt and the temperature is raised to 180±20°C, then an acid catalyst is added, the temperature is raised to 220±20°C, and the reaction is carried out under a reduced pressure of 0.08±0.02MPa for 2-3h, the reaction is terminated, and the temperature is lowered to obtain a polyester raw material.

[0012] By adopting the above technical solution, the desired high molecular weight polyester raw material can be obtained by controlling the reaction temperature and time as well as the ratio of raw materials. The addition of an acidic catalyst can significantly increase the transesterification reaction rate.

[0013] Optionally, the acid catalyst is added in an amount of 0.1-0.5 wt % of the raw material.

[0014] By adopting the above technical solution, when the acidic catalyst is added in the above proportion, the transesterification reaction rate can be significantly increased. When the amount of the acidic catalyst added is too little, the reaction rate is not significantly improved. When the amount added is too much, the content of the acidic catalyst in the reaction system is too high, resulting in the formation of distillation products by side reactions, which in turn inhibits the formation of the target product and is not conducive to obtaining the desired high molecular weight polyester. When the above proportion is added, the catalytic effect can be fully exerted without excessively inhibiting the reaction.

[0015] Optionally, in step S2, after the polyester raw material is heated and melted to 200-240°C, the obtained melt is extruded in multiple stages into extruded strips with a diameter of 5-10 mm, and then water-cooled in a nitrogen environment.

[0016] By adopting the above technical scheme, the polyester raw material is subjected to multi-stage extrusion to obtain small-diameter extruded strips, and then subjected to water-cooling pore-forming operation, which is more conducive to the construction of the pore structure of the final spherical ceramsite. The porosity of the porous ceramsite is ≥50%, and the specific surface area is>500m 2 / g, further improving the loading effect of porous ceramsite on nano-iron, and further improving the treatment effect of iron-based micro-electrolysis filler on wastewater.

[0017] Optionally, in step S3, during the atomic layer deposition process, the pressure is 0.01-0.05 MPa and the temperature is controlled to be 100-150° C., so that the nano-iron is evaporated and deposited on the porous ceramsite, wherein the amount of nano-iron particles added is 8-10% of the mass of the porous ceramsite.

[0018] By adopting the above-mentioned technical scheme, in the present application, the atomic layer deposition process is adopted to realize the load of nano iron on porous ceramsite, and the atomic layer deposition belongs to the self-limiting growth mode, so that the iron element is highly released and deeply penetrates into the ceramsite inside, and higher iron loading is realized, and the loading of iron in the present application is 3-5 times of the traditional loading process, and the loading of iron can be seriously controlled by this process, and the high dispersion of iron in porous ceramsite is ensured. For the pressure and temperature control during atomic layer deposition processing, under the pressure and temperature conditions, the effective release of nano iron is realized and fully reacts with porous ceramsite, so that nano iron is efficiently and uniformly deposited on the porous ceramsite surface, thereby realizing high loading and dispersion effect. When pressure and temperature are too low, it is not conducive to the release of nano iron, and when pressure and temperature are too high, it can cause the aggregation of part of nano iron, which is not conducive to dispersion.

[0019] Optionally, in step S3, nano-iron is obtained by the following method: Dissolve ferric nitrate in solvent water to obtain a ferric nitrate solution, adjust the pH value of the ferric nitrate solution to 3-5, and the concentration of the ferric nitrate solution to 0.05-0.2 mol / L; Pass hydrogen into the ferric nitrate solution to cause a reduction reaction, the hydrogen flow rate is 50-100 mL / min, the reaction temperature is 60-80°C, and the reaction time is 2-4 hours; After the reaction is completed, the nanometer iron particles with a particle size of 20-50 nm are obtained by centrifugation, washing and drying.

[0020] By adopting the above technical scheme, when preparing nano-iron, when the pH value is too low, the subsequent hydrogen reduction reaction is inhibited, and when the pH value is too high, it will cause the precipitation of iron ions; when the concentration of ferric nitrate is too low, it is not conducive to the reduction reaction, and when the concentration is too high, it will cause excessive aggregation of nano-iron; during the subsequent hydrogen reduction reaction, the hydrogen flow rate is controlled. When the hydrogen flow rate is too small, the supplied reducing agent is insufficient and the reaction is slow, and when the flow rate is too large, it will cause uneven mixing of the reaction system, and when the temperature is too low, the reaction rate slows down, and when the temperature is too high, it will cause product aggregation. The yield is high when the reaction time is too short, and excessive growth of the product occurs when the reaction time is too long. In the present application, the control of the pH and concentration of the ferric nitrate solution ensures the smooth progress of the nano-iron synthesis reaction, and the control of the flow rate, temperature and time during the hydrogen reduction process ensures the excellent synthesis effect of nano-iron, so that it has a larger load amount with the porous ceramsite, and the final wastewater treatment effect is better.

[0021] Optionally, in step S4, the specific operation of curing is: subjecting the modified ceramsite sprayed with the silica-modified polyaniline solution to microwave curing at a curing temperature of 150±10° C. for a heat preservation time of 5-10 min, and cooling to obtain an iron-based micro-electrolytic filler.

[0022] By adopting the above technical scheme, the modified ceramsite sprayed with silica-modified polyaniline solution is subjected to microwave curing, the coating cross-linking and curing is efficiently completed, the bonding force between the conductive polymer coating and the modified ceramsite substrate is enhanced, and the oxidative degradation of the conductive polymer under high temperature conditions is avoided.

[0023] Optionally, in step S4, the silica-modified polyaniline solution is prepared by the following method: The silica sol and the hydrochloric acid solution are mixed in a volume ratio of 1:(5-8) and then ultrasonically dispersed to obtain a diluted silica sol, and an ethanol solution of aniline is added under stirring, and the temperature is controlled to be less than 5±2° C. The amount of aniline added is 1.2-1.5 times the amount of silica sol added, and the amount of ethanol solution added is 3-5 times the amount of aniline added. At the same time, an ammonium persulfate solution is added in an amount of 3-8%, and the pH is adjusted to 1-2. The reaction is stirred for 1.5-2.5 hours. After the reaction stops, the mixture is allowed to stand, filtered, washed with water and dried to obtain silica-modified polyaniline; The prepared silica-modified polyaniline and ethanol are mixed in a mass ratio of 1:(10-15) to prepare a silica-modified polyaniline solution.

[0024] By adopting the above technical scheme, when preparing silica-modified polyaniline, the raw material ratio and reaction conditions are controlled to ensure the effective use of silica and polyaniline, and to generate modified polyaniline with excellent electrical conductivity. The addition of ammonium persulfate is also to adjust the reaction process and improve the product performance, and finally to obtain silica-modified polyaniline with better electrical conductivity, which can be used as a conductive coating for subsequent iron-based micro-electrolysis fillers, thereby improving the conductivity of the product, accelerating the electrolysis reaction process, and further improving the removal rate of pollutants in wastewater by iron-based micro-electrolysis fillers.

[0025] The subsequent control of the addition ratio of silica-modified polyaniline and ethanol is to prepare a silica-modified polyaniline solution with moderate concentration and viscosity as a spray coating for the outer layer of the subsequent iron-based micro-electrolytic filler. If the mass ratio is too low, the concentration of the obtained solution is too small, and it is not easy to form a uniform coating. If the ratio is too high, the viscosity of the solution is too large, which is not conducive to the spraying operation. The mass ratio in this application is selected to ensure that the solution has a higher content to form a uniform conductive coating, and also ensures that it has sufficiently low viscosity and good spraying performance.

[0026] In the second aspect, the present application provides an iron-based micro-electrolysis filler, which adopts the following technical solution: An iron-based micro-electrolysis filler is prepared by the preparation method.

[0027] By adopting the above technical scheme, the surface of the iron-based micro-electrolysis filler prepared by the preparation method in this application is coated with a conductive polymer coating, which solves the problem of direct contact between the iron material of the iron-based micro-electrolysis filler and the wastewater, thereby generating rust and plate formation. At the same time, the coating is a conductive polymer, which will not affect the micro-electrolysis effect of the iron-based micro-electrolysis filler. Using it in industrial wastewater treatment has a better treatment effect on wastewater.

[0028] In a third aspect, the present application provides an application of an iron-based micro-electrolysis filler, using the following technical solution: As described above, an iron-based micro-electrolysis filler is used in wastewater treatment.

[0029] By adopting the above technical solution, the iron-based micro-electrolysis filler in this application is used as the anode iron material and is directly used in combination with the external carbon plate. By changing the current addition form of the anode iron element, the problem of the current iron element directly contacting water and resulting in reduced treatment effect is solved.

[0030] In summary, this application has the following beneficial effects: 1. The iron-based micro-electrolytic filler in the present application is coated with a silicon dioxide-modified polyaniline solution on the surface, and then microwave-cured to form a firm conductive polymer protective coating, which is used for the pretreatment of industrial wastewater, improves the wastewater treatment effect of the micro-electrolytic filler, prevents the iron-based filler from rusting and agglomerating, improves the conductivity of the iron-based micro-electrolytic filler, better transmits current, thereby accelerating the electrolytic reaction, and has a better treatment effect on wastewater; 2. In the present application, polyester raw materials are melted at high temperature and then quickly cooled with water to generate a large number of tiny cracks and pores inside the polyester raw materials to form porous ceramsite with better pore structure, and then nano-iron is loaded on the surface of the porous ceramsite by atomic layer deposition. Compared with the prior art in which iron powder and carbon powder are directly physically mixed with auxiliary materials such as adhesives, after the iron on the surface of the filler is consumed, the internal iron is surrounded by clay, which reduces the reaction effect of the filler. In the present application, the polyester is formed into a skeleton structure through pore formation, and then nano-iron is loaded by atomic deposition. The above problems will not occur, and the wastewater treatment effect is better.

[0031] 3. The iron-based micro-electrolysis filler provided in the present application realizes a change in the current form of adding anode iron elements. The iron-based micro-electrolysis filler in the present application uses a porous structure formed by polyester as a carrier to realize the loading of nano-iron. The iron-based micro-electrolysis filler is used as an anode iron material and is used in conjunction with an external carbon plate to form a micro-electrolysis effect to achieve wastewater treatment. The conductive polymer protective coating is used to protect the iron element, thereby solving the problem that the treatment effect is reduced due to the viscosity surrounding it when it is in direct contact with water. The conductive polymer protective coating acts as an electron transfer channel, and the pore structure and hydrophilicity of the silica in the protective coating make it water permeable and can form a micro-electrolysis effect with the carbon source, while blocking impurities such as clay, thereby solving the current problem that the treatment effect is reduced due to the direct contact of the iron element with water. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0033] The nano iron particles used in the present application can be obtained from common commercial sources or by the following method. The nano iron in the following embodiments adopts the nano iron particles prepared in the following preparation examples.

[0034] Unless otherwise specified, the percentages in the following preparation examples and embodiments are all weight percentages.

[0035] Preparation Example 1 A method for preparing nano iron particles comprises the following steps: Dissolve ferric nitrate in solvent water to obtain a ferric nitrate solution, adjust the pH value of the ferric nitrate solution to 4, and the concentration of the ferric nitrate solution to 0.1 mol / L; Hydrogen was introduced into the ferric nitrate solution to cause reduction reaction, the hydrogen flow rate was 80 mL / min, the reaction temperature was 70°C, and the reaction time was 3 h; After the reaction is completed, the nanometer iron particles with a particle size of 20-50 nm are obtained by centrifugation, washing and drying.

[0036] Preparation Example 2 A method for preparing nano iron particles comprises the following steps: Dissolve ferric nitrate in solvent water to obtain a ferric nitrate solution, adjust the pH value of the ferric nitrate solution to 3, and the concentration of the ferric nitrate solution to 0.05 mol / L; Hydrogen was introduced into the ferric nitrate solution to cause reduction reaction, the hydrogen flow rate was 50 mL / min, the reaction temperature was 60°C, and the reaction time was 4 h; After the reaction is completed, the nanometer iron particles with a particle size of 20-50 nm are obtained by centrifugation, washing and drying.

[0037] Preparation Example 3 A method for preparing nano iron particles comprises the following steps: Dissolve ferric nitrate in solvent water to obtain a ferric nitrate solution, adjust the pH value of the ferric nitrate solution to 5, and the concentration of the ferric nitrate solution to 0.2 mol / L; Hydrogen was introduced into the ferric nitrate solution to cause reduction reaction, the hydrogen flow rate was 100 mL / min, the reaction temperature was 80°C, and the reaction time was 2 h; After the reaction is completed, the nanometer iron particles with a particle size of 20-50 nm are obtained by centrifugation, washing and drying.

[0038] The following Preparation Example 4-6 is an example of preparing a silica-modified polyaniline solution. In Preparation Example 4-6: the mass fraction of the silica sol is 10%, the hydrochloric acid solution is a hydrochloric acid solution with a molar concentration of 1 mol / L, and the mass fraction of the ammonium persulfate solution is 2%.

[0039] Preparation Example 4 Silica sol and hydrochloric acid solution are mixed in a volume ratio of 1:6 and then ultrasonically dispersed to obtain diluted silica sol, and aniline ethanol solution is added under stirring, the temperature is controlled to be 5°C, the amount of aniline added is 1.3 times the amount of silica sol added, the amount of ethanol added is 4 times the amount of aniline added, and ammonium persulfate solution is added at the same time, the amount of ammonium persulfate solution added is 5wt% of the mass of aniline, the pH is adjusted to 2, the reaction is stirred for 2h, and after the reaction stops, the mixture is allowed to stand, filtered, washed with water and dried to obtain silica-modified polyaniline; the obtained silica-modified polyaniline and ethanol are mixed in a mass ratio of 1:12 to obtain a silica-modified polyaniline solution.

[0040] Preparation Example 5 Silica sol and hydrochloric acid solution were mixed in a volume ratio of 1:5 and then ultrasonically dispersed to obtain diluted silica sol, and aniline ethanol solution was added under stirring, the temperature was controlled to be 5°C, the amount of aniline added was 1.2 times the amount of silica sol added, the amount of ethanol added was 3 times the amount of aniline added, and ammonium persulfate solution was added at the same time, the amount of ammonium persulfate solution added was 3wt% of the mass of aniline, the pH was adjusted to 1, the reaction was stirred for 1.5h, and after the reaction stopped, the mixture was allowed to stand, filtered, washed with water and dried to obtain silica-modified polyaniline; The prepared silica-modified polyaniline was mixed with ethanol in a mass ratio of 1:10 to prepare a silica-modified polyaniline solution.

[0041] Preparation Example 6 Silica sol and hydrochloric acid solution were mixed in a volume ratio of 1:8 and then ultrasonically dispersed to obtain diluted silica sol, and aniline ethanol solution was added under stirring, the temperature was controlled to be 5°C, the amount of aniline added was 1.5 times the amount of silica sol added, the amount of ethanol added was 5 times the amount of aniline added, and ammonium persulfate solution was added at the same time, the amount of ammonium persulfate solution added was 8wt% of the mass of aniline, the pH was adjusted to 1, the reaction was stirred for 2.5h, and after the reaction stopped, the mixture was allowed to stand, filtered, washed with water and dried to obtain silica-modified polyaniline; The prepared silica-modified polyaniline was mixed with ethanol at a mass ratio of 1:15 to prepare a silica-modified polyaniline solution.

[0042] Example 1 A method for preparing an iron-based micro-electrolysis filler comprises the following steps: S1. Preparation of polyester raw materials: using aromatic diacid and aliphatic diol as raw materials, the aromatic diacid is a mixture of terephthalic acid and isophthalic acid in a mass ratio of 60:40, and the aliphatic diol is a mixture of 1,4-butanediol and 1,6-hexanediol in a mass ratio of 55:45, and preparing the polyester raw materials through an ester exchange method; The specific operation of the ester exchange method is: aromatic diacid and aliphatic diol are mixed in a mass ratio of 1:1.1 as raw materials, heated to melt, and the temperature is raised to 180°C; then an acid catalyst is added, specifically p-toluenesulfonic acid, and the amount of the acid catalyst added is 0.5wt% of the raw material; the temperature is raised to 220°C, and the pressure is reduced to 0.08MPa. The generated low-boiling alcohols are removed during the decompression process, and the reaction is carried out under a reduced pressure of 0.08MPa for 2.5h, the reaction is terminated, and the temperature is lowered to room temperature to obtain a polyester raw material; S2, preparing porous ceramsite: heating and melting the polyester raw material in step S1 to 220° C. under nitrogen protection, extruding the melt obtained by heating and melting through a multi-stage extruder into an extruded strip with a diameter of 5-10 mm, and then rapidly cooling the extruded strip in a 3° C. water cooling tank under a nitrogen environment, cutting to obtain spherical ceramsite after water cooling and solidification, and drying to obtain porous ceramsite; S3, preparing modified ceramsite loaded with nano-iron: the nano-iron particles prepared in Preparation Example 1 and the porous ceramsite prepared in step S2 are placed in a low-pressure reactor, the pressure is controlled to be 0.03 MPa, the temperature is 120° C., and the evaporation deposition is carried out on the porous ceramsite by atomic layer deposition to prepare modified ceramsite, wherein the addition amount of the nano-iron particles is 9wt% of the mass of the porous ceramsite; S4, preparing iron-based micro-electrolytic filler: spray the silica-modified polyaniline solution prepared in Preparation Example 4 on the modified ceramsite prepared in step S3, and then transfer it to a microwave curing furnace (equipment power 2kw), heat it to 150°C for microwave curing, keep it warm for 8min, and then cool it naturally to obtain an iron-based micro-electrolytic filler with a silica-modified polyaniline conductive polymer film formed on the surface, and the thickness of the conductive polymer film on the surface of the micro-electrolytic filler is 100nm.

[0043] Example 2 A method for preparing an iron-based micro-electrolysis filler comprises the following steps: S1. Preparation of polyester raw materials: using aromatic diacid and aliphatic diol as raw materials, the aromatic diacid is a mixture of terephthalic acid and isophthalic acid in a mass ratio of 60:30, and the aliphatic diol is a mixture of 1,4-butanediol and 1,6-hexanediol in a mass ratio of 55:40, and preparing the polyester raw materials through an ester exchange method; The specific operation of the ester exchange method is as follows: aromatic diacid and aliphatic diol are mixed in a mass ratio of 1:1 as raw materials, heated to melt, and the temperature is raised to 160°C; then an acid catalyst is added, specifically p-toluenesulfonic acid, and the amount of the acid catalyst added is 0.1wt% of the raw material; the temperature is raised to 200°C, and the pressure is reduced to 0.06MPa. The generated low-boiling alcohols are removed during the decompression process, and the reaction is carried out under a reduced pressure of 0.06MPa for 2h, the reaction is terminated, and the temperature is lowered to room temperature to obtain a polyester raw material; S2, preparing porous ceramsite: heating and melting the polyester raw material in step S1 to 200° C. under nitrogen protection, extruding the melt obtained by heating and melting through a multi-stage extruder into an extruded strip with a diameter of 5-10 mm, and then rapidly cooling the extruded strip in a water cooling tank at 1° C. under a nitrogen environment, cutting to obtain spherical ceramsite after water cooling and solidification, and drying to obtain porous ceramsite; S3, preparing modified ceramsite loaded with nano-iron: placing the nano-iron particles prepared in Preparation Example 2 and the porous ceramsite prepared in step S2 in a low-pressure reactor, controlling the pressure to 0.01 MPa and the temperature to 100° C., and subjecting the nano-iron particles prepared in Preparation Example 2 and the porous ceramsite to evaporation deposition on the porous ceramsite by atomic layer deposition to prepare modified ceramsite, wherein the amount of the nano-iron particles added is 8 wt% of the mass of the porous ceramsite; S4, preparing iron-based micro-electrolytic filler: spray the silica-modified polyaniline solution prepared in Preparation Example 5 on the modified ceramsite prepared in step S3, and then transfer it to a microwave curing furnace (equipment power 2kw), heat it to 140°C for microwave curing, keep it warm for 5min, and then cool it naturally to obtain an iron-based micro-electrolytic filler with a silica-modified polyaniline conductive polymer film formed on the surface, and the thickness of the conductive polymer film on the surface of the micro-electrolytic filler is 100nm.

[0044] Example 3 A method for preparing an iron-based micro-electrolysis filler comprises the following steps: S1. Preparation of polyester raw materials: using aromatic diacid and aliphatic diol as raw materials, the aromatic diacid is a mixture of terephthalic acid and isophthalic acid in a mass ratio of 60:50, and the aliphatic diol is a mixture of 1,4-butanediol and 1,6-hexanediol in a mass ratio of 55:50, and preparing the polyester raw materials through an ester exchange method; The specific operation of the ester exchange method is: aromatic diacid and aliphatic diol are mixed in a mass ratio of 1:1.2 as raw materials, heated and melted, and the temperature is raised to 200°C; then an acid catalyst is added, specifically p-toluenesulfonic acid, and the amount of the acid catalyst added is 0.5wt% of the raw material; the temperature is raised to 240°C, and the pressure is reduced to 0.1MPa. The generated low-boiling alcohols are removed during the decompression process, and the reaction is carried out under a reduced pressure of 0.1MPa for 3h, the reaction is terminated, and the temperature is lowered to room temperature to obtain a polyester raw material; S2, preparing porous ceramsite: heating and melting the polyester raw material in step S1 to 240° C. under nitrogen protection, extruding the melt obtained by heating and melting through a multi-stage extruder into an extruded strip with a diameter of 5-10 mm, and then rapidly cooling the extruded strip in a 5° C. water cooling tank under a nitrogen environment, cutting to obtain spherical ceramsite after water cooling and solidification, and drying to obtain porous ceramsite; S3, preparing modified ceramsite loaded with nano-iron: the nano-iron particles prepared in Preparation Example 3 and the porous ceramsite prepared in step S2 are placed in a low-pressure reactor, the pressure is controlled to be 0.05 MPa, the temperature is 150° C., and the evaporation deposition is carried out on the porous ceramsite by atomic layer deposition to prepare modified ceramsite, wherein the addition amount of the nano-iron particles is 10wt% of the mass of the porous ceramsite; S4, preparing iron-based micro-electrolytic filler: spray the silica-modified polyaniline solution prepared in Preparation Example 6 on the modified ceramsite prepared in step S3, and then transfer it to a microwave curing furnace (equipment power 2kw), heat it to 160°C for microwave curing, keep it warm for 10min, and then cool it naturally to obtain an iron-based micro-electrolytic filler with a silica-modified polyaniline conductive polymer film formed on the surface, and the thickness of the conductive polymer film on the surface of the micro-electrolytic filler is 100nm.

[0045] Example 4 A method for preparing an iron-based micro-electrolysis filler is carried out according to the method in Example 1, except that in step S1, terephthalic acid is used as the aromatic diacid.

[0046] Example 5 A method for preparing an iron-based micro-electrolytic filler is carried out according to the method in Example 1, except that the aromatic diacid in step S1 is isophthalic acid.

[0047] Example 6 A method for preparing an iron-based micro-electrolysis filler is carried out according to the method in Example 1, except that the aliphatic diol in step S1 is 1,4-butanediol.

[0048] Example 7 A method for preparing an iron-based micro-electrolytic filler is carried out according to the method in Example 1, except that the aliphatic diol in step S1 is 1,6-hexanediol.

[0049] Example 8 A method for preparing an iron-based micro-electrolytic filler is carried out according to the method in Example 1, except that in step S2, after the polyester raw material is heated and melted, it is directly put into a water cooling tank for rapid water cooling without multiple stages of extrusion.

[0050] Comparative Example 1 A method for preparing an iron-based micro-electrolysis filler is carried out according to the method in Example 1, except that the operation of step S4 is not performed, that is, the surface of the modified ceramsite is not sprayed with a silicon dioxide-modified polyaniline solution, and the obtained modified ceramsite is directly used for wastewater treatment.

[0051] Comparative Example 2 A method for preparing an iron-based micro-electrolysis filler is carried out according to the method in Example 1, except that the specific operation of loading nano-iron with modified ceramsite in step S3 is: Dissolve ferric nitrate in water to prepare a ferric nitrate solution with a molar concentration of 0.1 mol / L; The porous ceramsite prepared in step S2 is immersed in the above-mentioned ferric nitrate solution for 40 minutes, and then the immersed porous ceramsite is dried to remove moisture, and then calcined at a calcination temperature of 110° C. and a calcination time of 1 hour to obtain modified ceramsite loaded with iron.

[0052] Comparative Example 3 A method for preparing an iron-based micro-electrolysis filler is carried out according to the method in Example 1, except that the specific operation of loading nano-iron with modified ceramsite in step S3 is: The nano-iron particles prepared in Preparation Example 1 and the porous ceramsite prepared in step S2 are ball-milled and mixed, and then calcined at 110° C. for 20-30 minutes and cooled to obtain modified ceramsite loaded with nano-iron.

[0053] Performance Testing First, the porosity and specific surface area of ​​the porous ceramsite prepared in step S2 in the embodiment and the comparative example were tested, and the test results are shown in Table 1 below.

[0054] Table 1: From the test results in Table 1 above, it can be seen that the porous ceramsite prepared by the preparation method of the present application has a high porosity, a porosity of ≥50%, and a specific surface area of ​​more than 500m 2 / g, combined with the test results of Example 1 and Examples 4-7, it can be seen that when isophthalic acid is not added to the aromatic diacid in Example 4, the porosity and specific surface area of ​​the porous ceramsite obtained in the end are reduced, and the addition of isophthalic acid helps to cause cracks in the water-cooling pore-forming process, thereby increasing its porosity; when isophthalic acid is used as the aromatic diacid in Example 5, its porosity and specific surface area are slightly reduced, and when only one aliphatic diol is used in Examples 6 and 7, the porosity and specific surface area of ​​the porous ceramsite obtained in the end are reduced. Combined with the test results of Example 1 and Example 8, it can be seen that the porosity and specific surface area of ​​the porous ceramsite obtained in step S2 are significantly reduced by directly water-cooling the polyester raw material after heating and melting.

[0055] In addition, the iron loading amount of the modified ceramsite loaded with nano-iron in step S3 in the embodiment and the comparative example was detected, and the conductivity of the iron-based micro-electrolysis filler prepared in step S4 was statistically analyzed. The test results are shown in Table 2 below: Table 2: From the test results in Table 2 above, it can be seen that the porous ceramsite in the embodiment of the present application has an iron loading capacity of 8-10% and an electrical conductivity of 80-120S / cm, which has excellent nano-iron loading capacity and electrical conductivity, and is more conducive to the subsequent wastewater treatment effect.

[0056] The iron-based micro-electrolysis filler prepared in the embodiments and comparative examples of the present application was used to treat wastewater. When treating the wastewater, the iron-based micro-electrolysis filler in the present application was placed on a carbon plate (carbon fiber plate), the carbon plate was used as a cathode carbon source, and the iron-based micro-electrolysis filler was used as an anode iron source. The amount of iron-based micro-electrolysis filler added was 5wt% of the wastewater, and the mass ratio of the carbon plate to the iron-based micro-electrolysis filler was 1:2. The initial COD concentration of the wastewater was 2500mg / L. The COD removal rate of the wastewater was tested for the iron-based micro-electrolysis filler, and the test results are shown in Table 3 below.

[0057] Table 3: Combined with the test results in Tables 1, 2 and 3, it can be seen that when the aromatic diacid in Example 4 is not added with isophthalic acid, the porosity and specific surface area of ​​the porous ceramsite finally obtained are significantly reduced, the loading amount of the iron element is also reduced, the final conductivity is also significantly reduced, and the COD removal rate for the wastewater is also low; when only one of the aromatic diacid and the fatty alcohol diacid is selected in Examples 5-7, the porosity and specific surface area are also reduced, the loading amount of the iron element is also reduced, the final conductivity is also reduced, and the COD removal rate for the wastewater is also reduced compared with Example 1. When the porosity and specific surface area of ​​the porous ceramsite in Example 8 are significantly reduced, the iron loading amount and conductivity are significantly reduced, and the wastewater treatment effect is significantly reduced.

[0058] The modified ceramsite in Comparative Example 1 is the same as that in Example 1, and the loading amount of nano-iron is the same. In Comparative Example 1, the surface of the modified ceramsite is not sprayed with a conductive polymer coating, and the conductivity of the final filler is significantly reduced, and the COD removal rate of the wastewater is low. Referring to the test results of Example 1, Comparative Example 2, and Comparative Example 3, it can be seen that when the modified ceramsite loads nano-iron by other methods, the loading amount of iron is much lower than the loading amount in Example 1 of the present application, and the conductivity is also significantly reduced, and the final treatment effect for the wastewater is poor. In Comparative Example 2, the loading method of impregnating porous ceramsite in an iron oxide precursor and then calcining it can be seen that although the loading amount of iron is relatively improved, its conductivity is low, which may be related to the distribution of iron.

[0059] In addition, in order to consider the service life of the iron-based micro-electrolysis filler in the present application, that is, the treatment stability after contact with water in the subsequent wastewater treatment process, the micro-electrolysis filler prepared in Example 1 of the present application and the comparative example was used to treat the wastewater for 10 cycles according to the above-mentioned wastewater treatment method (the iron-based micro-electrolysis filler is the anode iron source and the carbon plate is the cathode carbon source). The test results of the COD removal rate of the wastewater after the 3rd cycle, the 5th cycle, the 8th cycle and the 10th cycle are shown in Table 4 below.

[0060] Table 4: Cycle times 1 3 5 8 10 Example 1 COD removal rate after cycle / % 85 83 79 77 73 Comparative Example 1 COD removal rate after cycle / % 53 48 43 40 31 Comparative Example 2 COD removal rate after cycle / % 63 60 54 47 40 Comparative Example 3 COD removal rate after cycle / % 62 58 53 45 37 Referring to the test results in Table 4 above, it can be seen that the iron-based micro-electrolysis filler prepared in Example 1 of the present application still has a good COD removal rate for wastewater after 10 cycles of wastewater treatment, with less reduction in processing capacity and long service life. Moreover, after 10 cycles of treatment, no obvious rust formation phenomenon was observed, and the anti-rust performance was good. Referring to the test results of Comparative Example 1, the surface of the modified ceramsite in Comparative Example 1 was not sprayed with a conductive polymer coating, and the number of cycles of wastewater treatment was increased, and the wastewater treatment effect was significantly reduced. Moreover, it can be seen that after 5 cycles of treatment, there was a relatively obvious rust formation phenomenon, so the subsequent wastewater treatment effect was significantly reduced.

[0061] Referring to the test results of Comparative Examples 2 and 3, the effect of the iron-based micro-electrolysis filler obtained by loading nano-iron in Comparative Example 2 on wastewater treatment was significantly reduced after 5 cycles, and rust also occurred when it was recycled for 5 times, and the rust phenomenon was obvious after 8 cycles.

[0062] In summary, compared with the prior art, such as the micro-electrolysis filler disclosed in the CN104550939A patent, the iron powder and the activated carbon powder are prepared by a physical mixing and roasting step, without considering the porosity and conductivity of the micro-electrolysis filler during the actual wastewater treatment. The micro-electrolysis filler disclosed in the CN101838034A patent, although the porosity problem is solved by pore making, the method has fast iron consumption, and the addition of bentonite with a large specific gravity causes a large amount of sludge to be produced later, and after the iron on the filler surface is consumed, the internal iron is surrounded by clay, thereby reducing the reaction effect of the filler itself. In this application, an organic polyester is first prepared, and then a ceramsite with a larger porosity and specific surface area is constructed by water cooling to form pores, and then a high proportion and high uniformity of nano-iron load is achieved by an atomic layer deposition process, and then a silicon dioxide-modified polyaniline conductive polymer coating is coated, and microwave curing is used to form a firm conductive polymer protective coating, improve the product conductivity, accelerate the electrolysis reaction process, and improve the removal rate of pollutants in wastewater.

[0063] In summary, the iron-based micro-electrolysis filler provided in the present application realizes a change in the current form of adding anode iron elements. In the present application, the iron-based micro-electrolysis filler uses a porous structure formed by polyester as a carrier to realize the loading of nano-iron, and then the conductive polymer protective coating is used to realize the protection of the iron element, thereby solving the problem that it is directly in contact with water and is surrounded by viscosity, which reduces the treatment effect. The conductive polymer protective coating acts through its electron transfer channel, and the pore structure and hydrophilicity of silica in the protective coating make it water-permeable and can form a micro-electrolysis effect with the carbon source, while blocking clay and other debris, thereby solving the current problem that the treatment effect is reduced due to direct contact of iron elements with water. Therefore, the iron-based micro-electrolysis filler in the present application can be directly used in combination with an external carbon plate as an anode iron material.

[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing an iron-based micro-electrolysis filler, characterized in that: The following steps are involved: S1. Preparation of polyester raw materials: using aromatic diacids and aliphatic diols as raw materials, preparing polyester raw materials by ester exchange method; S2, preparing porous ceramsite: heating and melting the polyester raw material to 200-240°C under nitrogen protection, and then rapidly cooling it in water at 0-5°C, cutting it into spherical ceramsite after solidification by water cooling, and drying it to obtain porous ceramsite; S3, preparing modified ceramsite loaded with nano-iron: using atomic layer deposition to allow nano-iron to evaporate and deposit on porous ceramsite to obtain modified ceramsite; S4, preparing iron-based micro-electrolytic filler: spraying the silicon dioxide-modified polyaniline solution on the modified ceramsite prepared in step S3, and curing the solution to obtain the iron-based micro-electrolytic filler.

2. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S1, the aromatic diacid is a mixture of terephthalic acid and isophthalic acid, and the added mass ratio of terephthalic acid to isophthalic acid is 60: (30-50); The aliphatic diol is a mixture of 1,4-butanediol and 1,6-hexanediol, and the added mass ratio of 1,4-butanediol to 1,6-hexanediol is 55:(40-50); The added mass ratio of the aromatic diacid to the aliphatic diol is 1:(1-1.2).

3. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S1, the specific operation of transesterification is: The raw materials are heated to melt and the temperature is raised to 180±20°C, then an acid catalyst is added, the temperature is raised to 220±20°C, and the reaction is carried out under a reduced pressure of 0.08±0.02MPa for 2-3h, the reaction is terminated, and the temperature is lowered to obtain a polyester raw material.

4. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S2, the polyester raw material is heated and melted to 200-240°C, and the obtained melt is extruded into extruded strips with a diameter of 5-10 mm in multiple stages, and then water-cooled in a nitrogen environment.

5. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S3, during the atomic layer deposition process, the pressure is 0.01-0.05 MPa and the temperature is controlled to be 100-150° C., so that the nano-iron is evaporated and deposited on the porous ceramsite, wherein the amount of nano-iron particles added is 8-10% of the mass of the porous ceramsite.

6. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S3, nano-iron is obtained by the following method: Dissolve ferric nitrate in solvent water to obtain a ferric nitrate solution, adjust the pH value of the ferric nitrate solution to 3-5, and the concentration of the ferric nitrate solution to 0.05-0.2 mol / L; Pass hydrogen into the ferric nitrate solution to cause a reduction reaction, the hydrogen flow rate is 50-100 mL / min, the reaction temperature is 60-80°C, and the reaction time is 2-4 hours; After the reaction is completed, the nanometer iron particles with a particle size of 20-50 nm are obtained by centrifugation, washing and drying.

7. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S4, the specific operation of curing is: subjecting the modified ceramsite sprayed with the silica-modified polyaniline solution to microwave curing at a curing temperature of 150±10° C. for a heat preservation time of 5-10 min, and cooling to obtain an iron-based micro-electrolytic filler.

8. The method for preparing an iron-based micro-electrolytic filler according to claim 1, characterized in that: In step S4, the silica-modified polyaniline solution is prepared by the following method: The silica sol and the hydrochloric acid solution are mixed in a volume ratio of 1:(5-8) and then ultrasonically dispersed to obtain a diluted silica sol, and an ethanol solution of aniline is added under stirring, and the temperature is controlled to be less than 5±2°C, the amount of aniline added is 1.2-1.5 times the amount of silica sol added, and the amount of ethanol added is 3-5 times the amount of aniline added, and ammonium persulfate solution is added at the same time, and the amount of ammonium persulfate solution added is 3-8%, and the pH is adjusted to 1-2, and the reaction is stirred for 1.5-2.5h. After the reaction stops, the mixture is allowed to stand, filtered, washed with water and dried to obtain silica-modified polyaniline; The prepared silica-modified polyaniline and ethanol are mixed in a mass ratio of 1:(10-15) to prepare a silica-modified polyaniline solution.

9. An iron-based micro-electrolysis filler, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the iron-based micro-electrolysis filler as claimed in claim 9 in wastewater treatment.

Citation Information

Patent Citations

  • High efficiency hardening resistant micro-electrolysis material and preparation method thereof

    CN101838034A

  • Microelectrolysis packing as well as preparation method and application of microelectrolysis packing

    CN104550939A

  • Preparation method and application of iron-based multi-metal alloy micro-electrolysis filler

    CN109911992A

  • Method for preparing porous carbon material through polyester low-temperature carbonization

    CN111410184A

  • Preparation method of sludge-based biochar-supported nano-iron based on extracellular polymer

    JP7178535B1